Central exit exams improve student outcomes - Ludger Woessmann (IZA World of Labor, 2018)
Reaching the policy goal of improving student achievement by adding resources to the school system has often proven elusive. By contrast, ample evidence indicates that central exit exams constitute an important feature of a school system's institutional framework, which can hold students, teachers, schools, and administrators accountable for student outcomes. While critics point to issues such as teaching test-only skills, which may leave students ill-prepared for the real world, the evidence does not bear this out. Overall, central exams are related to better student achievement, favorable labor market outcomes, and higher economic growth.
Keywords: I28; J24; H52; 330; schools; education; exams; accountability; student achievement; earnings